Assessment of genetic diversity in pea (Pisum sativum L.) using morphological and molecular markers - Handerson, Chulet; Noren, S. K.; Wricha, Tyagi; Meetei, N. T.; Khanna, V. K.; Pattanayak, A.; Datt, Shiv; Choudhury, P. Ray; Kumar, Mukul (The Indian Journal of Genetics and Plant Breeding, 2017)
A total of 34 pea (Pisum sativum L.) genotypes including 7 adapted varieties, 6 popular local cultivars and 21 advanced breeding lines developed through crossing of elite cultivars were evaluated for genetic diversity and relatedness with 16 morphological traits and 15 SSR markers. Genotypes viz., DDR-23, E-6, Makuchabi and KPMR-885 were identified as early flowering while Rachna, IPFD 09-2, CAU FP-1, IPFD 1-10 and Pant P-136 were identified as high yielding. The number of alleles per SSR marker varied from 2 to 5 per locus. Polymorphic information content values (PIC) ranged from 0.105 to 0.560 per locus. Variability among groups (FIS=0.938) and variability within individuals (FIT=0.948) was low. The minimum and maximum molecular genetic distances were found to be 0.12 (Pant P-136 with VL-51) and 0.78 (E-6 with LP-4) respectively. Genotypes IPFD 09-2,HFP-620, Azad P-1, Matek, IPFD 1-10, CAU FP-1, IPFD 09-3, Pant P-136, Rachna, E-6, Matek and LP-3 showed high level of genetic diversity. Pea improvement through hybridization by utilizing diverse genotypes is suggested for breeding suitable genotypes for North Eastern region.